2016
DOI: 10.1097/pcc.0000000000000902
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Acquired and Congenital Heart Disease Patients and Its Relationship to Hospital Mortality and Lasting Neurologic Deficits

Abstract: A majority of patients with acquired or congenital heart disease who suffer stroke present while hospitalized and without focal neurologic findings. In-hospital mortality is associated with inotropes, cardiac procedures, lack of seizure, and parenchymal hemorrhage. The majority of survivors have lasting neurologic deficits associated with longer hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
3
12
0
1
Order By: Relevance
“…One explanation for this could be that stroke can explain more of the deterioration of functional abilities cases, but is often under-recognised. A recent study from Cheng showed that 41% of stroke diagnosis in children with heart disease was found only on surveillance imaging studies 30 . Similar findings were reported by Bellinger et al; they found that 40% of strokes in adolescents surviving the Fontan were initially missed by clinical assessment alone.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…One explanation for this could be that stroke can explain more of the deterioration of functional abilities cases, but is often under-recognised. A recent study from Cheng showed that 41% of stroke diagnosis in children with heart disease was found only on surveillance imaging studies 30 . Similar findings were reported by Bellinger et al; they found that 40% of strokes in adolescents surviving the Fontan were initially missed by clinical assessment alone.…”
Section: Discussionsupporting
confidence: 67%
“…A recent study from Cheng showed that 41% of stroke diagnosis in children with heart disease was found only on surveillance imaging studies. 30 Similar findings were reported by Bellinger et al; they found that 40% of strokes in adolescents surviving the Fontan were initially missed by clinical assessment alone. In children, initial symptoms of stroke are often not clear, 31,32 and children with stroke often "grow into their deficits".…”
supporting
confidence: 82%
“…Childhood AIS resulting from cardiac disease occurs in the inpatient setting more often than the outpatient setting and involves younger children, with a median age of 6 months to 3 years. [68][69][70][71] These children present with seizures in up to 40% and hemiparesis in 36% to 75% and are clinically covert in 14% to 40%. Braun et al 72 found that cardioembolic stroke may present with abrupt onset compared with a stuttering or fluctuating presentation in children with stroke caused by arteriopathy.…”
Section: Tbd 2019mentioning
confidence: 99%
“…Neonates and children with cardiac disease comprise one of the highest risk populations for pediatric arterial ischemic stroke (AIS), with a reported annual incidence rate ranging from 132 of 100,000 children to one of 100 children 1,2 compared with two to eight of 100,000 in the general pediatric population. 3,4 This risk persists beyond childhood.…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, life-saving interventions such as cardiac surgery, cardiac catheterization, and mechanical circulatory support come with the cost of AIS as a potential complication. 2,[7][8][9][10][11] Infection and thrombosis are also complications of cardiac interventions and influence AIS risk. 12 Infection has been shown to play a major role in childhood AIS pathogeneses of all causes, including spontaneous cardioembolic stroke.…”
Section: Introductionmentioning
confidence: 99%